Variety earliness effect on field drying of biomass sorghum. (August 2018) - Colauzzi, M.; Serra, P.; Amaducci, S.
Abstract: A major constraint to the use of biomass sorghum varieties ( Sorghum bicolor (L.) Moench) to generate electricity by direct combustion is the high biomass moisture content at harvest that, under unfavourable weather conditions during field drying limits the possibility to achieve a suitable moisture content for baling. In this work, the CropSyst model was calibrated and validated with data collected in experimental trials conducted in the Po Valley (northern Italy). It was then used to simulate biomass production of three sorghum varieties of contrasting earliness (early, medium-late, and late). In order to simulate the dynamics of biomass moisture content during field drying, a specific model, "sorghum haying model", was developed and validated. The two models combined were used to simulate, for three sorghum varieties of contrasting earliness (early, medium-late and late), biomass production and the probability to achieve during field drying a biomass moisture content suitable for baling. In a long term simulation (140 years), the late sorghum variety achieved the highest dry biomass production (16.5 Mg ha −1 ) followed by the medium-late (15.4 Mg ha −1 ) and early (15.1 Mg ha −1 ) variety. The early variety had the highest probability (0.66) of being baled at a moisture content ≤ 18%, followed by the medium-late (0.53) and late (0.37) varieties. The early variety, also having the shortest average field drying (9.2 days), was considered the most suitable for the selected environmental conditions. Highlights: A model to simulate field drying of sorghum was developed, calibrated and validated. Late sorghum variety had the highest dry matter production at harvest. Duration and dynamics of field drying were affected by variety earliness. Early variety had the highest probability to be baled at suitable moisture content. Early variety had the shorted drying period and permanence in the field.